Proceedings of the 2015 ITiCSE on Working Group Reports 2015
DOI: 10.1145/2858796.2858800
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in K-9 Computer Science Education

Abstract: This exploratory study focuses on concepts and their assessment in K-9 computer science (CS) education. We analyzed concepts in local curriculum documents and guidelines, as well as interviewed K-9 teachers in two countries about their teaching and assessment practices. Moreover, we investigated the 'task based assessment' approach of the international Bebras contest by classifying the conceptual content and question structure of Bebras tasks spanning five years. Our results show a variety in breadth and focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…Interaction (Human-Computer Interaction, HCI), systems and society Analyses of the Bebras tasks used in the 2014 contest were conducted according to the cognitive skills' domains (Bloom taxonomy): this showed that the most tasks demonstrated higher-order thinking skills in the Bloom's taxonomy: Understanding, Applying, Analysing and Evaluating (Dagiene & Stupuriene, 2014). In another analysis examining the topics of all Bebras tasks used between 2010 and 2014, the most commonly occurring computational thinking topics were algorithms (66%) and data representation (38%), followed by abstraction (16%) (Barendsen et al, 2015).…”
Section: Computational Thinking and Bebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction (Human-Computer Interaction, HCI), systems and society Analyses of the Bebras tasks used in the 2014 contest were conducted according to the cognitive skills' domains (Bloom taxonomy): this showed that the most tasks demonstrated higher-order thinking skills in the Bloom's taxonomy: Understanding, Applying, Analysing and Evaluating (Dagiene & Stupuriene, 2014). In another analysis examining the topics of all Bebras tasks used between 2010 and 2014, the most commonly occurring computational thinking topics were algorithms (66%) and data representation (38%), followed by abstraction (16%) (Barendsen et al, 2015).…”
Section: Computational Thinking and Bebrasmentioning
confidence: 99%
“…The topic of networks is very broad; it can be found in various forms in many countries' informatics curricular (Barendsen et al, 2015). At school level, this topic could cover topologies, communication, networking protocols, security and the way that the internet is structured.…”
Section: Learning About Networkmentioning
confidence: 99%
“…They also observe that on one hand the term "coding" has a broader meaning in CS (e.g. in cryptography or in information theory), and on the other hand it is often used to indicate the stage of software development when programs are actually written [10,1,2]. In other words, "coding" is considered as a narrower concept excluding important phases like analysis, design, testing, debugging [3].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Bebras is about concept in computer science and computational thinking. Barendsen et al (2015) show that it is possible to identify concepts on programming in various questions in the Bebras task pool. Izu, Mirolo, Settle, Mannilla, and Stupuriene (2017) describe how the goals of computational thinking are reflected in Bebras tasks.…”
Section: Content Difficultymentioning
confidence: 99%